Controlling Practitioner–patient Relationships in Acupuncture Trials: A Systematic Review and Meta-Regression. Issue 2 (June 2013) - Prady, Stephanie L; Burch, Jane; Crouch, Simon; MacPherson, Hugh
Background: In trials, 'therapist intensive' complex interventions are typically delivered over time, during which a relationship between the practitioner and participant may develop. Such relationships are sometimes criticised as obscuring any 'true' treatment effect. Limiting interactions is one strategy that might be used to try to control for the effect of a therapeutic relationship. Objectives: We conducted systematic review into the rationale, methods and effects of constraining relationships in controlled trials and cohort studies of acupuncture, including studies published before 2008 with an update citation search in 2010. Methods: We searched six databases without keyword restrictions. Meta-analysis and meta-regression were used to explore the effect of relationship constraint on pain outcomes. Results: Eighty-one of 785 (10.3%) trials reported constraining relationships. Most did not state the reason for constraint, describe the nature of the limitation, provide information on how the constrained relationship was monitored or note protocol adherence. Where a reason was reported, this was primarily to maintain participant blinding, rarely was it stated that the constraint was to control the therapeutic relationship. We found no evidence of an effect of constraint on pain outcomes (percentage heterogeneity explained, p=0.89). These results were robust to variation in trial quality and design. Conclusions: Acupuncture trials appear to be constrained mostly to try to prevent participant unblinding to their allocated treatment, not to control the therapeutic relationship. The apparent lack of monitoring and negligible effects on pain outcomes of the included trials indicate the need for more high-quality randomised controlled trials investigating the effect of constraint.